Evaluation of Vibrations of Ginning and Pressing Machinery in Cotton Ginneries - Arude, V G; Manojkumar, T S; Shukla, S K (Journal of Agricultural Engineering, 2009)
India has over 4000 cotton ginneries in which thousands of worker’s work under difficult conditions. Cotton ginneries contains various types of machinery-each a source of noise and vibration. The basic machinery in a ginnery are double roller gin (DR), pre-cleaner, lint cleaner and baling press besides automatic material handling systems. The vibration levels were measured on different commercial ginning machinery. The intensity of vibration for different parts of double roller gin in terms of acceleration, velocity and displacement varied between 3.29 - 47.85 m/s², 0.25-5.85 cm/s and 13 x10?5-28.53 x10?5 m, respectively. The coefficient of variation (CV) for acceleration varied from 48.8 to 69.7 per cent. The maximum vibrations were observed on hopper, swing lever, gearbox and seed chute of DR gin. The average acceleration, velocity and displacement for different models of DR gin was found to be 18.47 m/s², 1.55 m/s and 9.72 x10?5 m with the corresponding CV values of 35.28 %, 16.06% and 37.13%, respectively. The average acceleration for pre-cleaner and lint cleaner was 5.48 m/s² and 5.25 m/s² with the corresponding CV values of 16.79% and 21.26%, respectively. The different parts of the baling press were found to accelerate between 0.51–6.24 m/s² with an average acceleration of 2.80 m/s². The CV for different parts of the baling press was 74.78 per cent. The support columns of the press were more affected by vibrations followed by platform, power pack and lint condenser. Ginning machines were thus subjected to high vibrations, and above the permissible limit. Hence, appropriate measures need to be taken to lower the level of vibrations to the acceptable level for comfort of the workers.